2007
DOI: 10.1038/labinvest.3700533
|View full text |Cite
|
Sign up to set email alerts
|

H3 histamine receptor agonist inhibits biliary growth of BDL rats by downregulation of the cAMP-dependent PKA/ERK1/2/ELK-1 pathway

Abstract: Histamine regulates many functions by binding to four histamine G-coupled receptor proteins (H1R, H2R, H3R and H4R). As H3R exerts their effects by coupling to Ga i/o proteins reducing adenosine 3 0 , 5 0 -monophosphate (cAMP) levels (a key player in the modulation of cholangiocyte hyperplasia/damage), we evaluated the role of H3R in the regulation of biliary growth. We posed the following questions: (1) Do cholangiocytes express H3R? (2) Does in vivo administration of (R)-(a)-(À)-methylhistamine dihydrobromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(159 citation statements)
references
References 65 publications
(99 reference statements)
6
152
1
Order By: Relevance
“…As we have previously shown, 25 after BDL there is a marked increase in intrahepatic biliary mass and cholangiocyte proliferation compared with sham-operated rats. Following treatment with cromolyn sodium, IBDM was significantly decreased as shown by immunohistochemistry (quantified in the bottom left panel) and real-time PCR for CK-19 ( Figure 1).…”
Section: Treatment With Cromolyn Sodium Decreases Bdlinduced Ibdm Andmentioning
confidence: 50%
See 3 more Smart Citations
“…As we have previously shown, 25 after BDL there is a marked increase in intrahepatic biliary mass and cholangiocyte proliferation compared with sham-operated rats. Following treatment with cromolyn sodium, IBDM was significantly decreased as shown by immunohistochemistry (quantified in the bottom left panel) and real-time PCR for CK-19 ( Figure 1).…”
Section: Treatment With Cromolyn Sodium Decreases Bdlinduced Ibdm Andmentioning
confidence: 50%
“…We also evaluated the expression of CK-19 (the cholangiocyte-specific marker 25,28 ) by real-time PCR. Our cultured mast cell line expressed high levels of HDC, MAO-B, chymase, tryptase and c-kit but had virtually no expression of CK-19 ( Figure 7).…”
Section: Treatment With Cromolyn Sodium In Vitro Decreases Mast Cell mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been largely demonstrated that H 3 R is mostly expressed in the central and, to a lesser extent, in the peripheral nervous system. Only a small number of experimental observations have showed its presence on non-neuronal cell types such as rodent fundic mucosa endocrine cells [26], cholangiocytes [37], pancreatic β-cells [38], and in the human bronchial epithelial cell line BEAS-2B [39]. Therefore, our data add a new non-neuronal localization of the H 3 R, contributing to the hypothesis that the H 3 R could also mediate nonneuronal histamine effects.…”
Section: Discussionmentioning
confidence: 68%